Mesopelagic Fish Protein Hydrolysates and Extracts: A Source of Novel Anti-Hypertensive and Anti-Diabetic Peptides - Naik, Azza S.; Whitaker, R. D.; Albrektsen, S.; Solstad, Runar G.; Thoresen, Lars; Hayes, Maria (Frontiers in Marine Science, 2021)
The abundance of fish and zooplankton (1 × 109 tonnes to 7 × 1010 tonnes) in the mesopelagic zone of the ocean is a source of novel raw materials that provides opportunities for sustainable new product development. Peculiar conditions of light and pressure in this ecological zone and the position of the specific organisms in the marine food chain results in diversity in bio-composition. Mesopelagic fish are an underutilised resource, rich in proteins and omega-3 oils, and present opportunities to develop novel feed, food and functional food ingredients and products. However, there is also a need to ensure that this resource is not overfished and is processed to optimize the catch in line with sustainability goals. There is therefore a need to establish sustainable bioprocessing technologies to yield value added products from mesopelagic fish species. In the present study, various protein extracts from the mesopelagic fish Maurolicus muelleri (M) and Meganyctiphanes norvegica (Northern Krill) (K) and combinations of proteins from these species (C) were generated using hydrolysis methods. Protein hydrolysates were generated using different enzymes including Alcalase, endocut-01, endogenous M/K enzymes and FoodPro PNL. Hydrolysates were characterised and assessed for their ability to inhibit enzymes important in diseases associated with metabolic syndrome. The ability of generated hydrolysates to inhibit enzymes including Angiotensin-1-converting enzyme (ACE-1; EC. 3.4.15.1) associated with blood pressure regulation, Acetylcholinesterase (AChE; EC 3.1.1.7) associated with maintenance of the nervous system, and Dipeptidyl peptidase IV (DPP-IV; EC 3.4.14.5) linked with development of type-2-diabetes, was determined. These mesopelagic fish were also transformed into fishmeal, hydrolysates, fish-silage, and aqueous extracts (AQ) and screened for bioactivities using the same bioassays. A hydrolysate from M. muelleri generated using FoodPro PNL (M1) inhibited the ACE-1 enzyme by 89.56% when assayed at a concentration of 1 mg/ml compared to the positive control Captopril©. The study shows that targeting processing of mesopelagic fish have potential to generate hydrolysates for use in the prevention of type-2-diabetes and hypertension.